集“不贞”和“忠贞”于一身 探析《聊斋志异》中女性的矛盾性 = An investigation of the contradictory infidelity females in “Strange Tales of Liao Zhai” (Liao Zhai Zhi Yi) - 黄薇谕 Huang, Weiyu (2011)
蒲松龄在《聊斋志异》中塑造了众多的女性形象，其中不少是集“不贞”和“忠贞”于一身的女性。贞节向来是女性最为看重、誓死守护的节操，更是女子“妇德”的象征。然而，在蒲松龄的笔下，一些“忠贞不渝”的女性却曾经有过一段“不贞”的过往，使她们的形象更具复杂和矛盾性。在无奈的处境下，有的女子被迫放弃贞操；有的却在毫无威逼下，大胆、自主、甚至怀有目的地“不贞”。而仔细探究这“不贞”的行为下，不难发现在她们的内心深处其实隐藏了一颗散发着“真、善、美”的炽热之心。本文将通过文本细读的方式，试图探析处在善与恶灰色地带的这群女子，“不贞”和“忠贞”如何交织而集于一身，以至于既反映了人性的矛盾，更展现了不凡的人性光辉。Pu Songling created many female images in the “Strange Tales of Liao Zhai” (Liao Zhai Zhi Yi), many of which contained a contradictory infidelity and fidelity character. Chastity has always been the most important moral principle of females and a symbol of “Women’s Virtue (Fu De)”, which must be uphold at all times. However, in Pu Songling’s writings, some faithful women actually had a marital disloyal past, causing their characters to be more complex and contradicting. Under helpless circumstances, some women were forced to forgo their chastity while others opted for infidelity under no pressure and even with a certain motive. With careful investigation of this unfaithfulness, it is not hard to discover the “genuine (zhen), kindness (shan), beauty (mei)” hidden deep inside their hearts. Through analyzing the novel, this paper will explore the women situated in the grey boundaries of good and bad, investigating how infidelity and fidelity interweave and together reveal an extraordinary human goodness while reflecting the contraction in humanity.